The role of TASK-1 and TRPV1 channels in the male reproductive system - Dawon Kang; Eun-A Ko (Journal of Animal Reproduction and Biotechnology)
The mammalian testis is a highly organized organ essential for male reproduction. Its structure comprises seminiferous tubules lined with Sertoli cells, which support spermatogenesis, surrounded by peritubular myoid cells. Within the connective tissue framework lie the Leydig cells, which synthesize testosterone in response to luteinizing hormone. Research has highlighted the importance of various ion channels and proteins in testicular function. The TWINK-related acid-sensitive potassium channel 1 (TASK-1), a two-pore channel, is vital for several physiological functions in the testis. Furthermore, Leydig cells uniquely express several key proteins, including c-kit, and platelet-derived growth factor receptor α. The co-expression of these proteins, including TASK-1, in Leydig cells suggest the presence of complex regulatory mechanisms critical for modulating testosterone production, release, and overall testicular function. Transient receptor potential vanilloid-1 (TRPV1), a member of the transient receptor potential channel family, also plays a crucial role in testicular function, influencing processes such as sensory function, steroidogenesis, and sperm function. Hormonal fluctuations and aging affect both the presence and function of TRPV1. This channel is thought to contribute programmed cell death within the testes, particularly impacting Leydig cell survival. Notably, testosterone appears to counteract these detrimental effects by downregulating TRPV1 expression, indicating a complex interplay between TRPV1, testosterone, and overall testicular function. Therefore, we aim to discuss the critical role of ion channels, specifically focusing on TASK-1 and TRPV1 channels, in the physiological and pathophysiological functions of testicular cells.